ANALISIS KETAHANAN PANGAN DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN PROVINSI RIAU - Cindy Rosalina; Tibrani (UIR Press, 2023)
Food security is a condition of achieving an individual's diet on national level with adequate food availability for both in quantity and quality, safe, diverse, nutritious, fair and affordable. Food security consisted of three aspects, namely (1) availability is availability of sufficient food both in quantity and quality; (2) access, namely the affordability of food or having the resources to obtain food and; (3) utilization, namely proper use based on basic nutritional knowledge. Three aspects are used as benchmarks for achieving food security. This study aims to analyze: the status of food security in terms of access to food in Pangkalan Kerinci District, status of food security in terms of food utilization and combined index of food security at the level of Village/Kelurahan level in Pangkalan Kerinci District. This research was conducted for six months, from May to November 2022. The data were used secondary data for various years as needed, especially data for 2020 as a basis for analysis because the latest year's data was incomplete or not available. The results showed that the condition of food security from the aspect of food availability was in the status of food security with an index of 0.19. The condition of food security from the aspect of food access, Pangkalan Kerinci District is in a very food insecure status with a combined index value of food access of 1.01. The condition of food security from the aspect of food utilization, Pangkalan Kerinci District is in a very food insecure status with a combined index value of food utilization of 1.54. The food condition of Pangkalan Kerinci District in 2020 is based on a combined index analysis of the three aspects of food security, namely access to food and utilization of the food used which is in a relative condition or food security status is very food insecure with a combined index value of 2.75. The village/ward of Kuala Terusan has the largest combined index value of 2.45 and the village/ward of Pangkalan Kerinci Kota has the smallest index value of 0.01.